2014
DOI: 10.1007/s00240-014-0727-3
|View full text |Cite
|
Sign up to set email alerts
|

How do the residual fragments after SWL affect the health-related quality of life? A critical analysis in a size-based manner

Abstract: This study aimed at evaluating the possible effects of residual fragments (RF) after shockwave lithotripsy (SWL) on the health-related quality of life (QOL) of the patients on a size-related basis. Eighty six patients with RF after SWL were divided into three groups: Group 1 (n:30 with fragments ≤ 2 mm), Group 2 (n:21 2-≤ 4 mm) and Group 3 (n:35 > 4 mm). During a 3-month follow-up, spontaneous passage rates, emergency department visits, mean analgesic required, additional procedures and the QOL were all evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In this respect, the relationship between SWL procedure and quality of life has been investigated in several studies. [3,[14][15][16] Conclusion drawn from these studies may be summarized as physicians responsible for treatment of stones in the urinary system should not focus only on the rate of stonefree status obtained, and should also take into account possible affect on patients' social and economic status and their quality of life of the treatment administered. More invasive procedures performed following initial procedure in order to increase the rate of stone-free success may negatively affect patients' quality of life and cause increased anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the relationship between SWL procedure and quality of life has been investigated in several studies. [3,[14][15][16] Conclusion drawn from these studies may be summarized as physicians responsible for treatment of stones in the urinary system should not focus only on the rate of stonefree status obtained, and should also take into account possible affect on patients' social and economic status and their quality of life of the treatment administered. More invasive procedures performed following initial procedure in order to increase the rate of stone-free success may negatively affect patients' quality of life and cause increased anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals undergoing SWL, the presence of residual fragments, particularly those exceeding 2mm, can also exert significant effects on HRQOL. 24 Encouraging patients to actively participate in decisions regarding stone treatment is crucial. Patient decision-making aids have proven to enhance patients' understanding of various surgical options for ureteral stone removal.…”
Section: Hrqol In Surgical or Procedural Managementmentioning
confidence: 99%
“…Patients with larger fragments had greater requirements for analgesia and had lower QoL scores at 1 and 3 months. 63 Furthermore, fragment size predicts future stone growth and complications: in patients with RF after ureteroscopy, Chew et al reported that fragments between 2–4 mm were associated with stone growth but not with complications or re-intervention, whilst fragments larger than 4mm were associated with both growth and complications. 64 The goal of managing the increasing burden of stone disease is therefore to choose the correct procedure for the correct stone in the appropriate patient to maximise the chance of a genuinely stone free patient (or at least with RF less than 2 mm in size) to provide the best event-free long-term result.…”
Section: Stones and Endourology (Ds)mentioning
confidence: 99%